Energy metabolism in cachexia. (19th March 2019) - Rohm, Maria; Zeigerer, Anja; Machado, Juliano; Herzig, Stephan
Abstract: Cachexia is a wasting disorder that accompanies many chronic diseases including cancer and results from an imbalance of energy requirements and energy uptake. In cancer cachexia, tumor‐secreted factors and/or tumor–host interactions cause this imbalance, leading to loss of adipose tissue and skeletal and cardiac muscle, which weakens the body. In this review, we discuss how energy enters the body and is utilized by the different organs, including the gut, liver, adipose tissue, and muscle, and how these organs contribute to the energy wasting observed in cachexia. We also discuss futile cycles both between the organs and within the cells, which are often used to fine‐tune energy supply under physiologic conditions. Ultimately, understanding the complex interplay of pathologic energy‐wasting circuits in cachexia can bring us closer to identifying effective treatment strategies for this devastating wasting disease. Abstract : This review discusses the contribution of different organs to energy wasting in cachexia, as well as the complex interplay of futile energy‐wasting circuits between organs and within cells.